Organizational Commitment: The Key to Reduce Employees’ Resistance to Change - Pena-Sanchez, Rolando (Archives of Business Research, 2023)
This report recognizes some of the most important causes of resistance to organizational change; some of which are related to the skills of employees and others to the company’s communication procedures, which affects the work performance of employees and the image of the organization. To achieve the organization’s objectives, the importance of structural change management, organizational culture, and the ability to modify strategies when circumstances warrant is also documented: First to contain, and then to reduce resistance to organizational change. The report includes a comparison of the proportion of successful and unsuccessful efforts regarding resistance to "organizational change"; a process that can be conceived as a "dialectical progression", whose main support is the institutional commitment implicit in the mission, vision, and core values of the organization. A nonparametric statistical technique: Jonckheere-Terpstra test was selected to perform the data analysis.